Ministerial decree 29/2016 with regard to the controls of representing the public money in the joint ventures in which the holding companies and subsidiaries subject to the ministry of public business sector have shareholdings / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 33/2016